Effect of 150 keV Ti+ ion implantation on the structural, optical, and electrical properties of nonstoichiometric WO2.72 thin films. (January 2022) - Kriti,; Kaur, Puneet; Chalotra, Surbhi; Nongjai, Razia; Sulania, Indra; Kandasami, Asokan; Singh, D.P.
Highlights: Electron-beam evaporated nonstoichiometric WO2.72 thin films implanted with low energy 150 keV Ti + ions. Implantation results in defragmentation and realignment of grains. Ti implants cause bandgap narrowing along with increased Urbach energy. Reduced PL emissions manifest the occurrence of more nonradiative and Auger-type recombination. Semiconductor to metal transition observed in thin film implanted with the highest Ti + -ions fluence. Abstract: WO2.72 thin films were deposited on fluorine-doped tin oxide substrates using the e-beam evaporation technique, and 150 keV Ti + ions were implanted at various fluences. The structural studies of these thin films confirm the presence of P21/m monoclinic phase. After implantation, the intensities of X-ray peaks varied significantly, and atomic force microscopy images revealed changes in grain size with realignments and surface roughness. The redshift observed in the calculated bandgaps is due to the bandgap narrowing effect. The photoluminescence (PL) study shows the decrease in the PL intensity after implantation due to an increase in nonradiative and Auger recombination effects. The electrical studies exhibit the semiconductor to metal transition in Ti-implanted films at the highest ion fluence. The decreasing trend of resistivity, accompanied by the decrease in the carrier concentration, and the higher mobility is understood based on various scattering mechanisms. Graphical abstract: Image, graphical abstract